The influence of James and Darwin on Cajal and his research into the neuron theory and evolution of the nervous system - Monte Ferreira, Francisco R.; Nogueira, Maria I.; DeFelipe, Javier (Frontiers in Neuroanatomy, 2014)
In this article we discuss the influence of William James and Charles Darwin on the thoughts of Santiago Ramón y Cajal concerning the structure, plasticity, and evolution of the nervous system at the cellular level. Here we develop Cajal’s notion that neuronal theory is a necessary condition to explain the plasticity of neural connections. Although the roots of the term “plasticity” in reference to neuroscience are not completely clear, Cajal was an important figure in the propagation and popularization of its use. It is true that he carried out a large number of studies throughout his career in favor of the neuronal theory, but perhaps one of the most interesting aspects of his studies was his innovative capacity to interpret structure as being the result of evolutionary mechanisms, i.e., natural selection. This capacity would ultimately lead Cajal to the conclusion that, in relation to the histology of the nervous system, such selection occurs in the establishment of connections between cells. The present article is divided into five sections: (1) Learning and general notions of organic plasticity in the 19th century; (2) The idea of “mental” plasticity proposed by James; (3) Neuronal theory and “structural” plasticity: general considerations; (4) Evolutionary factors of the nervous system in Cajal’s work; and (5) Final considerations.